The role of economical T.v programs in shaping the trends of the Iraqi investor Iraqi satellite channel model - Nadia Ahmed Hassoun Al – Tamimi (Genius Journals, 2023)
The title of the research: "The role of economic programs in the Iraqi channel, the in shaping the trends of the Iraqi investor." A field study on the investor public. The study examined the role played by Al-Iraqiya TV channel in shaping the trends of the Iraqi investor. This research is classified into descriptive research, using the survey method. The researcher used the research tools (questionnaire and measurement) A sample of (460) was selected in a deliberate sample to reveal this role
Keywords: economic; sample; deliberate; survey